Identifikasi Motivasi Belajar Siswa pada Pembelajaran IPS Kelas VI di Sekolah Dasar - Wahidin, Wahidin; Sasongko, Rambat Nur; Kristiawan, Muhammad; Riyanto, Muklis; Susanto, Edy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the motivation of learning learners in social sciences (IPS) class VI at SD Negeri Sukaraja. The research method used is survey research with the purpose of exploration. The data collection in this study used questionnaires through google forms. The sample in this study amounted to 27 respondents who were grade VI students at SD Negeri Sukaraja. The results showed that the motivation of learning grade VI students in ips learning from 27 students surveyed, 26 of them responded that 84.6% of teachers conveyed IPS learning materials well so that students were enthusiastic in the learning process. In conclusion, the motivation of learning students in IPS learning is very good, students of grade VI SD Negeri Sukaraja are very enthusiastic in carrying out the learning process of IPS. Most of the students are serious in carrying out the learning process of IPS. Key words: Learning Motivation, Social Studies, Students